2010
DOI: 10.1037/a0018501
|View full text |Cite
|
Sign up to set email alerts
|

The effects of visual magnification and physical movement scale on the manipulation of a tool with indirect vision.

Abstract: Modern tools often separate the visual and physical aspects of operation, requiring users to manipulate an instrument while viewing the results indirectly on a display. This can pose usability challenges particularly in applications, such as laparoscopic surgery, that require a high degree of movement precision. Magnification used to augment the view and, theoretically, enable finer movements, may introduce other visual-motor disruptions due to the apparent speed of the visual motion on screen (i.e., motion sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
3
19
1
1
Order By: Relevance
“…Accot & Zhai, 2001;Kwon, Choi, & Chung, 2011;Lin, Radwin, & Vanderheiden, 1992;MacKenzie & Riddersma, 1994). Others have reported that performance improves with gain (Bohan, McConnell, Chaparro, & Thompson, 2010;Gibbs, 1962;Huysmans, De Looze, Hoozemans, Van der Beek, & Van Dieën, 2006;Johnsgard, 1994;Thompson, McConnell, Slocum, & Bohan, 2007;Van Doorn, Unema, & Hendriks, 2005). Yet others have reported that performance decreases with gain (e.g.…”
Section: Introductionmentioning
confidence: 84%
“…Accot & Zhai, 2001;Kwon, Choi, & Chung, 2011;Lin, Radwin, & Vanderheiden, 1992;MacKenzie & Riddersma, 1994). Others have reported that performance improves with gain (Bohan, McConnell, Chaparro, & Thompson, 2010;Gibbs, 1962;Huysmans, De Looze, Hoozemans, Van der Beek, & Van Dieën, 2006;Johnsgard, 1994;Thompson, McConnell, Slocum, & Bohan, 2007;Van Doorn, Unema, & Hendriks, 2005). Yet others have reported that performance decreases with gain (e.g.…”
Section: Introductionmentioning
confidence: 84%
“…Additionally, we are pursuing studies using other psychomotor tasks such as the Fitts' pointing task (Fitts 1954;Fitts & Peterson, 1964) to compare the bandwidth of the devices (e.g., MacKenzie, 1992) as well as examine the separate physical and visual characteristics of the pointing task (e.g., Bohan, McConnell, Chaparro, & Thompson, 2010).…”
Section: Future Studiesmentioning
confidence: 99%
“…Future studies are planned that include adding stressors such as noise and vibration to simulate the complex environments in which these controls are sometimes used. Additionally, we are pursuing studies using other psychomotor tasks such as the Fitts' pointing task (Fitts 1954;Fitts & Peterson, 1964) to compare the bandwidth of the devices (e.g., Mac-Kenzie, 1992) as well as examine the separate physical and visual characteristics of the pointing task (e.g., Bohan, McConnell, Chaparro, & Thompson, 2010).…”
Section: Future Studiesmentioning
confidence: 99%
“…This results in a small movement of the tip of the grasper appearing as a large movement on the monitor (DeLucia & Griswold, 2011). Gain distortions have been shown to be associated with movement error (Bohan, McConnell, Chaparro, & Thompson, 2010). Fourth, sometimes the camera is rotated to the right or left of the surgeon's hands, resulting in visuomotor rotations.…”
Section: Introductionmentioning
confidence: 99%